2009
DOI: 10.1093/hmg/ddp569
|View full text |Cite
|
Sign up to set email alerts
|

Loss of nuclear poly(A)-binding protein 1 causes defects in myogenesis and mRNA biogenesis

Abstract: The nuclear poly(A)-binding protein 1 (PABPN1) is a ubiquitously expressed protein that plays a critical role in polyadenylation. Short expansions of the polyalanine tract in the N-terminus of PABPN1 lead to oculopharyngeal muscular dystrophy (OPMD), which is an adult onset disease characterized by eyelid drooping, difficulty in swallowing and weakness in the proximal limb muscles. Although significant data from in vitro biochemical assays define the function of PABPN1 in control of poly(A) tail length, little… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
130
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(143 citation statements)
references
References 44 publications
13
130
0
Order By: Relevance
“…This study also shows drastic accumulation of polyadenylated RNA in the nucleus of PABPN1-depleted cells, suggesting a role for PABPN1 in mRNA export. 41 Interestingly, this robust mRNA export defect was not accompanied by mRNA hyperadenylation, a phenotype that was previously associated with mRNA export defects in yeast, fruit flies and mammalian cells. 7,29,42,43 In Drosophila, specific pabp2 mutants also show shorter poly(A) tails using total RNA or individual mRNAs.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…This study also shows drastic accumulation of polyadenylated RNA in the nucleus of PABPN1-depleted cells, suggesting a role for PABPN1 in mRNA export. 41 Interestingly, this robust mRNA export defect was not accompanied by mRNA hyperadenylation, a phenotype that was previously associated with mRNA export defects in yeast, fruit flies and mammalian cells. 7,29,42,43 In Drosophila, specific pabp2 mutants also show shorter poly(A) tails using total RNA or individual mRNAs.…”
Section: Resultsmentioning
confidence: 65%
“…40 Although these aforementioned evidence are mostly indirect, more recent gene silencing experiments using primary mouse cells support the role of PABPN1 as a general mRNA polyadenylation factor. 41 The fact that the hypoadenylation phenotype of PABPN1-depleted cells did not significantly alter the expression levels of poly(A) + RNAs is intriguing, however, given the important role of the 3' poly(A) tail in mRNA expression. This study also shows drastic accumulation of polyadenylated RNA in the nucleus of PABPN1-depleted cells, suggesting a role for PABPN1 in mRNA export.…”
Section: Resultsmentioning
confidence: 99%
“…34,35 Briefly, mice were sacrificed and TA, gastrocnemius, and extensor digitorum longus muscles were isolated. Excess connective tissues and fat were cleaned in sterile PBS followed by mincing of skeletal muscle in Dulbecco's Modified Eagle's Medium and enzymatic dissociation with 0.1% pronase.…”
Section: Primary Myoblast Isolation and Fusion Assaysmentioning
confidence: 99%
“…Biochemical studies on PABPN1 led to a model in which the protein promotes efficient polyadenylation during mRNA synthesis (7). Although a role for PABPN1 in modulating poly(A) tail length is supported by studies in primary mouse myoblasts (8), studies in human cell lines have recently revealed novel functions for PABPN1. One study demonstrated that PABPN1 modulates the use of alternative polyadenylation sites by occluding access to weak polyadenylation signals for a select group of human genes (9,10).…”
mentioning
confidence: 99%